1970
DOI: 10.1042/cs0380359
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Pressure and Exaggerated Natriuresis in Essential Hypertension

Abstract: 1. Intrarenal pressure, estimated by measurement of wedged renal vein pressure, was elevated in patients with essential hypertension. Despite increased afferent arteriolar resistance, glomerular pressure was elevated indicating that the higher systemic pressure in essential hypertension is transmitted beyond the arterioles and accounts for elevation of intrarenal pressure.2. During hypertonic saline loading in hypertensives, renal arteriolar resistance falls, resulting in further increase in intrarenal pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
49
0
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 24 publications
(30 reference statements)
2
49
0
2
Order By: Relevance
“…Lowenstein et al ' found an elevated intrarenal venous pressure (IRVP) in patients with essential hypertension, and also observed that the augmented natriuretic response to saline volume expansion was associated with an exaggerated increase in IRVP in these patients. 8 These findings have been considered as evidence for an increased peritubular capillary hydrostatic pressure in human essential hypertension compensating for the postulated sodium retaining mechanisms and partly explaining the "resetting" of the pressure natriuresis. 8 " 11 We have not been able to confirm the findings of Lowenstein et al that saline volume expansion increases the IRVP in normal man, 1* and our preliminary observations in patients with essential hypertension 1 ' did not suggest any abnormality of IRVP.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lowenstein et al ' found an elevated intrarenal venous pressure (IRVP) in patients with essential hypertension, and also observed that the augmented natriuretic response to saline volume expansion was associated with an exaggerated increase in IRVP in these patients. 8 These findings have been considered as evidence for an increased peritubular capillary hydrostatic pressure in human essential hypertension compensating for the postulated sodium retaining mechanisms and partly explaining the "resetting" of the pressure natriuresis. 8 " 11 We have not been able to confirm the findings of Lowenstein et al that saline volume expansion increases the IRVP in normal man, 1* and our preliminary observations in patients with essential hypertension 1 ' did not suggest any abnormality of IRVP.…”
mentioning
confidence: 99%
“…8 These findings have been considered as evidence for an increased peritubular capillary hydrostatic pressure in human essential hypertension compensating for the postulated sodium retaining mechanisms and partly explaining the "resetting" of the pressure natriuresis. 8 " 11 We have not been able to confirm the findings of Lowenstein et al that saline volume expansion increases the IRVP in normal man, 1* and our preliminary observations in patients with essential hypertension 1 ' did not suggest any abnormality of IRVP. In our present study we examine the IRVP in antidiuresis and during sustained volume expansion in essential hypertension to assess the hydrostatic and oncotic forces acting in the postglomerular capillaries in these experimental conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Also, they have pharmacological evidence that the progression of glomerulosclerosis can be retarded by lowering intraglomerular pressure in rats. 19 -20 Lowenstein et al 21 found that wedged renal vein pressure is increased in hypertensive patients. This observation suggests that increased systemic arte- rial pressure is transmitted through the glomerulus to the renal vein.…”
Section: Figure 2 P/o/ Of Changes In Quantity Of Antihypertensive Drmentioning
confidence: 99%
“…4 The main focus of the Renal Laboratory in the Department of Medicine was to investigate the role of the kidney in the pathogenesis of essential hypertension. With evidence that renal artery stenosis was characterized by excessive sodium reabsorption, 5,6 Baldwin and others in the laboratory sought to determine whether the abnormalities in the renal excretion of sodium might be a feature of essential hypertension.…”
mentioning
confidence: 99%